Kualitas Pelayanan dalam Menangani Keluhan Peserta pada BPJS Kesehatan di Kota Jambi - Kinanti Eksa Putri; Dwi Kurniawan; Fitri Widiastuti (MASMAN Master Manajemen, 2026)
The research entitled Service Quality in Handling Complaints of BPJS Kesehatan Participants in Jambi City aims to investigate the quality of BPJS Kesehatan services in handling participant complaints and identify improvement efforts that are carried out in a sustainable manner. This study uses a qualitative approach with a phenomenological design to understand participants' experiences, perceptions, and satisfaction levels in depth. Data was collected through interviews, observations, and documentation of participants and service officers, then analyzed through the stages of data reduction, data presentation, and conclusion drawing systematically. The results of the study show that the quality of service at BPJS Kesehatan Jambi City is relatively good, characterized by adequate facilities, relatively clear service procedures, information transparency, and high responsiveness of officers in following up on complaints. However, accessibility challenges are still found, especially for participants who have limitations in the use of digital technology and access to information. Improvement efforts such as the development of digital-based complaint channels, optimization of face-to-face services, improving officer competence, and consistently implementing standard operating procedures reflect the institution's commitment to improving the quality of public services effectively and sustainably.